POLA PENGELUARAN WISATAWAN DI BANGKA BELITUNG - Sitorus, Berlian (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 1 (2019): Jurnal IPTA (July 2019)DO - 10.24843/IPTA.2019.v07.i01.p05, 2019)
Tourism is the main sectors for driven a sustainable economy through the multiplier impacts of tourism expenditures. However, we don't know yet how much the impact of changes in the structure and the expenditure on income. This paper aims to explore data from Tourism Satellite Account (TSA) in the Province of Bangka Belitung Islands in 2011 and 2017. Results from this study found the increasing 346 percent of tourist spending for increased 200% visitor thus it was concluded that tourism activities had a major impact on income creation. This means that tourism activities in Bangka Belitung have been integrated into the regional economic system and have a tremendous impact on the lives of the people of Bangka Belitung.